Search 75,787 tutors
FIND TUTORS
Ask a question
0 0

solve the quadratic equation by completing the square

Tutors, please sign in to answer this question.

1 Answer

When completing you must isolate the terms that have x. 
x2 - 2x = 2
Then you take the coefficient of the "b" term (2x), divide it by 2 and then square it giving you the result of 1. You then add that to both sides so your equation should now read
x2 - 2x + 1 = 3
Now simply factor and solve!
(x-1)(x-1) = 3
x - 1 = sqrt(3)

x= sqrt(3) + 1